Analisis Kesesuaian Perairan untuk Keramba Jaring Apung di Kecamatan Sirah Pulau Padang Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Rangga Bayu Kusuma Haris; Indah Anggraini Yusanti (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Haris et al, 2019. The Analysis of Water Suitability for Floating Net Sprouts in Sirah Pulau Padang, Ogan Komering Ilir District, South Sumatra Province. JLSO 8(1):20-30.The purpose of this study is to analyze the level of water suitability of the floating net sprouts in sirah pulau padang, ogan komering river, Serdang Menang Village, OKI South Sumatra Regency based on water physical and chemical parameters. This study was conducted on July - August 2018 at the Komering River, Ulak Jermun village, Terusan Menang Village, and Mangun Jaya Village, OKI District, South Sumatra. The data of sampling was divided into 3 stations, they were; station 1 was Ulak Jermun Village (3 ° 18'45.48 "LS and 104 ° 53'5.32" BT), station 2 was Terusan Menang Village (3 ° 17'14.13 "LS and 104 ° 52'46.78 "BT), and station 3 was Mangun Jaya village (3 ° 18'14.92" LS and 104 ° 52'59.48 "BT). The data of Samples were tested at the chemical laboratory in Palembang Public Water Fisheries and Extension Research Institute directly. The results of the study was for Station 1, Station 2, and Station 3 with a value was  48% with a good feasibility information. The results of measurements of water quality parameters, the pH was about 6.6 - 6.7, temperature was about from 24., 53 - 26.93oC, DO 3.93 - 4.36 mg / l, ammonia was about 0.78 - 0.16 mg / l, water brightness was about from 34.67 - 43.33 cm, CO2 4.53 - 5.03 mg / l, depth 2.36 - 2.47 m, current velocity was about 0.38 - 0.44 m / s, nitrate was about 0.37 - 0.439 mg / l, phosphate was about 0.009 - 0.225 mg / l and the bottom substrate of water was mud.